The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1016/0014-5793(90)81055-s
|View full text |Cite
|
Sign up to set email alerts
|

Partial hepatectomy and mediators of inflammation decrease the expression of liver α2‐HS glycoprotein gene in rats

Abstract: Liver mRNA levels of two acute phase reactant (APR) proteins, %-HS glycoprotein (a major negative APR) and q-acid glycoprotein (a major positive APR) were measured in male rats at different times after the administration of turpentine, of tumor necrosis factor, or following partial hepatectomy. In every case, a marked decrease in mRNA levels of a;-HS glycoprotein was observed which reached a maximum at 24 h. A concomitant increase of q-acid glycoprotein mRNA levels was observed under the same conditions. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
1
2

Year Published

1992
1992
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 17 publications
3
28
1
2
Order By: Relevance
“…A time-course study of these hepatic mRNA levels following a TO challenge is shown in Figure 3. The fetuin-A mRNA level was transiently down-regulated as expected from former reports [23,36] while the mRNA level for a positive APP used as a control, namely the IαIH4P protein of the Inter-α-Inhibitor family, was transiently up-regulated as described previously [37]. The level of fetuin-B mRNA was down-regulated as early as 9 h post-TO, reached a 2-fold decrease at days 1-2 and returned to a normal value beyond 1 week, which on the whole is similar to the variations seen for the fetuin-A mRNA level.…”
Section: Inflammation-associated Changes In Hepatic Level Of Fetuin-bsupporting
confidence: 85%
See 2 more Smart Citations
“…A time-course study of these hepatic mRNA levels following a TO challenge is shown in Figure 3. The fetuin-A mRNA level was transiently down-regulated as expected from former reports [23,36] while the mRNA level for a positive APP used as a control, namely the IαIH4P protein of the Inter-α-Inhibitor family, was transiently up-regulated as described previously [37]. The level of fetuin-B mRNA was down-regulated as early as 9 h post-TO, reached a 2-fold decrease at days 1-2 and returned to a normal value beyond 1 week, which on the whole is similar to the variations seen for the fetuin-A mRNA level.…”
Section: Inflammation-associated Changes In Hepatic Level Of Fetuin-bsupporting
confidence: 85%
“…The hepatic level of fetuin-A mRNA is down-regulated during an APR in rat [23,26] and our preliminary data indicated that the hepatic level of fetuin-B mRNA also varies following an inflammatory challenge in rat [27]. Therefore, we compared in more detail the changes of both mRNA levels of both genes in liver during an APR in rat.…”
Section: Inflammation-associated Changes In Hepatic Level Of Fetuin-bmentioning
confidence: 96%
See 1 more Smart Citation
“…Protein and/or DNA sequences have been reported for human (Lee et al, 1987), cow (Dziegielewska et al, 1990), sheep and pig , rat (Ohnishi et al, 1993), mouse (Yamamoto and Sinohara, 1993;Yang et al, 1992), Mongolian gerbil (Goto et al, 1997), rabbit (Osawa et al, 1997), and Habu snake (Yamakawa and Omori-Satoh, 1992) fetuins. AHSG is also one of the few negative acute phase reactants in humans (Lebreton et al, 1979) and rats (Daveau et al, 1990), whereas fetuin is a positive acute phase protein in cattle and mice (Yang et al, 1992). To clarify the physiological role of AHSG, the structure and properties should be studied in more animal species and compared.…”
mentioning
confidence: 99%
“…Nồng độ của AHSG trong huyết thanh thường giảm đi khi xuất hiện các triệu chứng viêm nhiễm hay các khối u ác tính [2]. Các nghiên cứu sử dụng phương pháp phân tích hóa sinh truyền thống đã cho thấy, sự giảm của nồng độ protein này ở bệnh nhân động mạch vành [10].…”
Section: +unclassified